Class Number One Problem for a Non-richaud-Degert Type Family of Real Quadratic Fields - Mahapatra, Nimish Kumar (Sarajevo Journal of Mathematics, 2024)
We study the class number one problem for a one parameter family of real quadratic fields Q(d), where d=100m^2+ 28m+2 and m is a positive integer. We show that there is no such field with class number one.